Pembuatan Aplikasi Penduga Berat Badan Sapi dengan Memanfaatkan Kamera Smartphone Berbasis Android - Aris Riyanto; Rinta Kridalukmana; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2016)
Weight is an important parameter in cattle breeding. In determining price of cattle, weight must be known accurately. If the estimation of weight is not accurate, this will cause losses for farmers. On the other hand, traditional farmers don’t have enough money to buy the expensive conventional scale. Even in cattle’s market, more common ranchers estimate cattle's weight only by their feelings. This does not only cause greater potential’s loss but also does not have a scientific foundation. This study aims to help farmers in estimating cattle's weight. Cattle's weight can be estimated by knowing Within Cow's Breast (WCB) as described in DAHAGA formula discovered by Winoto and friends in 2015. This study aims to implement the DAHAGA formula that has accuracy until 97.9% into an android application. The application runs by using the camera to estimate the object’s height to determine the real value of WCB. This calculation is performed using template matching method which compares the real object with image caught on camera. After WCB parameter known, then the application will execute DAHAGA formula and issued cattle’s weight as a final result. This application is expected to be an easy, inexpensive and accurate solution for farmers in estimating cattle’s weight.